Amorphous rigidification and cooperativity drop in semi−crystalline plasticized polylactide. (24th April 2020) - Varol, N.; Delpouve, N.; Araujo, S.; Domenek, S.; Guinault, A.; Golovchak, R.; Ingram, A.; Delbreilh, L.; Dargent, E.
Abstract: Plasticization of amorphous polylactide shifts the glass transition and extends its temperature range of crystallization to lower temperatures. In this work, we focus on how low−temperature crystallization impacts the mobility of the amorphous phase. Plasticizer accumulates in the amorphous phase because it is excluded from the growing crystal. The formation of rigid amorphous fraction is favored by the low crystallization temperature. It reaches values up to 50% in plasticized polylactide. The increase in the content of rigid amorphous fraction coincides with both the increase of free volume quantified by positron annihilation lifetime spectroscopy, and the decrease in the cooperativity length obtained from the temperature fluctuation approach. The drop of cooperativity is interpreted in terms of mobility gradient due to the amorphous rigidification. Graphical abstract: Image 1 Highlights: Plasticized PLA has been crystallized 20 °C above its glass transition. Crystallization induces a shift of the glass transition to lower temperatures. Fastest amorphous rigidification in plasticized PLA. High increase of free volume during non-isothermal crystallization. Cooperativity drops with the amorphous rigidification.